IL-10 Protects Neurites in Oxygen-Glucose-Deprived Cortical Neurons through the PI3K/Akt Pathway - Lin, Longzai (PLoS One, 2015)
IL-10, as a cytokine, has an anti-inflammatory cascade following various injuries, but it remains blurred whether IL-10 protects neurites of cortical neurons after oxygen-glucose deprivation injury. Here, we reported that IL-10, in a concentration-dependent manner, reduced neuronal apoptosis and increased neuronal survival in oxygen-glucose-deprived primary cortical neurons, producing an optimal protective effect at 20ng/ml. After staining NF-H and GAP-43, we found that IL-10 significantly protected neurites in terms of axon length and dendrite number by confocal microscopy. Furthermore, it induced the phosphorylation of AKT, suppressed the activation of caspase-3, and up-regulated the protein expression of GAP-43. In contrast, LY294002, a specific inhibitor of PI3K/AKT, reduced the level of AKT phosphorylation and GAP-43 expression, increased active caspase-3 expression and thus significantly weakened IL-10-mediated protective effect in the OGD-induced injury model. IL-10NA, the IL-10 neutralizing antibody, reduced the level of p-PI3K phosphorylation and increased the expression of active caspase-3. These findings suggest that IL-10 provides neuroprotective effects by protecting neurites through PI3K/AKT signaling pathway in oxygen-glucose-deprived primary cortical neurons.